Relationship Of Physical Activity With Sleep Quality In Class XI Students Of SMA Kharisma Bangsa And View Of Islam - Dani Mulya Arrafi; Sri Wahyu Herlinawati; Firman Arifandi (Junior Medical Journal, 2022)
Background: Sleep quality is a measure by which individuals find it easier to initiate sleep and maintain sleep. As many as 63% of Indonesian teenager’s sleep quality is not met. One of the factors that affect the quality of sleep is physical activity. Physical activity is defined as any activity produced by skeletal muscles and requires energy expenditure. In Indonesia, the proportion of physical activity aged 10 years classified as less active in general is 26.1 percent. This study aims to determine the relationship between physical activity and the quality of class XI students at SMA Kharisma Bangsa.Methods: This type of research is analytic with a cross sectional approach and the method of determining the sample is simple random sampling. The sample in this study were students of class XI SMA Kharisma Bangsa with a total of 51 students.Results: From the results of statistical analysis, 22 (43.1%) respondents with physical activity did light physical activity with 3 (5.9%) of them having good sleep quality and 19 (37.3%) respondents having poor sleep quality; 17 (17.9%) respondents did moderate physical activity with 8(15.7%) having good sleep quality and 9 (17.6%) having poor sleep quality; 12 (23.5%) did strenuous physical activity with 9 (17.6%) of them having good sleep quality and 3 (5.9%) having poor sleep quality. The results of the Chi-Square test showed a p-value of 0.002 (0.05) which indicated a relationship between physical activity and sleep quality for students of class XI SMA Kharisma Bangsa.Conclusion: There is a significant relationship between physical activity and sleep quality in class XI students of SMA Kharisma Bangsa. The advice that can be given is to maintain the quality of sleep by doing enough physical activity